2000
DOI: 10.1007/s002130000473
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/orphanin FQ (N/OFQ) induces a quasi-morphine abstinence syndrome in the rat

Abstract: Nociceptin/orphanin FQ (N/OFQ) is a neuropeptide that exerts antiopiate effects under some circumstances, and there is evidence that it contributes to opiate tolerance. This raises the question, might N/OFQ also contribute to opiate dependence and abstinence? Twenty-two male Sprague-Dawley rats were cannulated in the third ventricle and challenged 7 days later by third ventricle injection of 50, 200 or 1,000 ng N/OFQ or saline alone. Each rat was observed under "blind" conditions for 30 min beginning 15 min af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…N/OFQ and NOP also appear to be directly involved in drug reinforcement, dependence and/or motivation (Devine et al 1996;Ciccocioppo et al 1998Ciccocioppo et al , 2000Malin et al 2000). While OFQ itself does not produce conditioned place preference or aversion, it does alter place conditioning produced by ethanol (EtOH) and morphine (Ciccocioppo et al 1998;Murphy et al 1999).…”
Section: Introductionmentioning
confidence: 98%
“…N/OFQ and NOP also appear to be directly involved in drug reinforcement, dependence and/or motivation (Devine et al 1996;Ciccocioppo et al 1998Ciccocioppo et al , 2000Malin et al 2000). While OFQ itself does not produce conditioned place preference or aversion, it does alter place conditioning produced by ethanol (EtOH) and morphine (Ciccocioppo et al 1998;Murphy et al 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Although Malin et al [112] found N/OFQ (i.c.v.) produced morphine-like abstinence signs, N/OFQ (i.c.v.)…”
Section: Drug Dependencementioning
confidence: 96%
“…In naive rats, nociceptin induces abstinence-like signs in a dose dependent manner [148], and fails to precipitate withdrawal symptoms [82] or attenuate naloxone-precipitated abstinence signs [149] in morphine-dependent rats. Ueda et al [138] reported that, after a 3 day morphine treatment, mice lacking the ORL1 receptor or ddY mice receiving the antagonist J-113397 exhibit a significant reduction in naloxoneprecipitated withdrawal signs (jumps, paw tremor, backward locomotion, sniffing, defecation) in comparison to controls, suggesting that activation of the nociceptin receptor contributes to the development of physical dependence.…”
Section: Dependencementioning
confidence: 99%